The economic role of women in agricultural and rural development: promoting income generation - Booth, J.G.; Protais, M.J. (Technical Centre for Agricultural and Rural Cooperation, 2000)
The seminar objective was to develop strategies for gender equality through exchanging information on women's roles and opportunities in rural development, with the emphasis on income-generating activities.